2008
DOI: 10.1063/1.2982585
|View full text |Cite
|
Sign up to set email alerts
|

Graphene segregated on Ni surfaces and transferred to insulators

Abstract: We report a surface segregation approach to synthesize high quality graphenes on Ni under ambient pressure. Graphenes were segregated from Ni surfaces by carbon dissolving at high temperature and cooling down with various cooling rates. Different segregation behaviors were identified, allowing us to control the thickness and defects of graphene films. Electron microscopy and Raman spectroscopy studies indicated that these graphenes have high quality crystalline structure and controllable thickness. Graphenes w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
974
0
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,202 publications
(1,020 citation statements)
references
References 17 publications
11
974
0
6
Order By: Relevance
“…However, the produced graphene strongly interacts with the substrate, hindering fabrication of electrically isolated monolayer graphene. On the other hand, CVD growth of graphene on catalytic metals, such as Cu [21] and Ni [17,21,311], is a promising approach for efficient large-scale production of defect-free graphene with controllable number of layers. Moreover, the resulting monolayer graphene can be easily transferred to arbitrary substrates [312].…”
Section: Disorders In Graphene Structurementioning
confidence: 99%
“…However, the produced graphene strongly interacts with the substrate, hindering fabrication of electrically isolated monolayer graphene. On the other hand, CVD growth of graphene on catalytic metals, such as Cu [21] and Ni [17,21,311], is a promising approach for efficient large-scale production of defect-free graphene with controllable number of layers. Moreover, the resulting monolayer graphene can be easily transferred to arbitrary substrates [312].…”
Section: Disorders In Graphene Structurementioning
confidence: 99%
“…However, the CVD on metal process is less suitable for device fabrication as the graphene layers must be transferred onto a semiconducting or SI substrate [17]. These transferred graphene layers tend to be both defected and contaminated as a result of the transfer process, thus resulting in graphene which is not suitable for device oriented applications [18].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have reported the direct synthesis of large-area single-or multilayer graphene on transition metal substrates by chemical vapor deposition (CVD) [17][18][19][20][21][22]. An advantage of CVD is that graphene can be transferred to other substrates because some transition metals can be etched by acid solution [17,18]. However, the deposition temperatures required for thermal CVD are generally higher than 800°C, and a relatively long deposition time is needed.…”
mentioning
confidence: 99%
“…However, large-area graphene is difficult to obtain using adhesive tape, mechanical cleavage and chemical exfoliation [12][13][14]. It has been reported that largearea graphene can be grown epitaxially on single crystal SiC, but SiC substrates are expensive and it is difficult to exfoliate or transfer the graphene from SiC to another substrate because of the strong cohesive strength of the graphene/SiC interface and the extreme chemical stability of SiC [14][15][16][17]. Many researchers have reported the direct synthesis of large-area single-or multilayer graphene on transition metal substrates by chemical vapor deposition (CVD) [17][18][19][20][21][22].…”
mentioning
confidence: 99%
See 1 more Smart Citation